Corrigendum to "Which factor is more important for the welfare of broiler chickens: Intensity or duration of episodic heat stress?" [J. Therm. Biol. 99 (2021) 102981]. (April 2022) - Iyasere, O.S.; Bateson, M.; Beard, A.P.; Guy, J.H.
Abstract: Due to the effects of global warming, there is a predicted increase in the frequency, intensity and duration of heat waves in the future. Little is known of how this could affect the welfare of broiler chickens. Sixty-four broiler chickens were subjected to either high heat stress (HHS; 32 o C, 70% RH for 3 h), moderate heat stress (MHS; 30 o C, 70% RH for 6 h), or normal conditions (NC: 20 o C, 50% RH for 6 h) for two consecutive days. Half the birds had been subjected to anaesthesia and fitted with a body temperature-ID chip placed in the breast muscle. Core body temperature (CBT) was taken during pre-heat stress (PrHS), at the end of 3 h (3HS) and 6 h (6HS) of heat stress using a pocket reader and used to estimate change in CBT (ΔCBT). Surface body temperatures (SBTs) from under the wing (WT), feet (FT), cloaca (CLT) and comb (CT) were also measured, along with blood parameters, feed intake, daily weight gain and mortality. Data were analysed using General Linear Model and simple linear regression. At 3HS, CBT/ΔCBT and all SBTs showed this trend: HHS > MHS > NC (P<0.001). Blood pH, pCO2, iCa, HCO3 - and TCO2 showed the same trend: HHS, MHS > NC (P<0.05). Comparing HHS for 3 h with MHS and NC for 6 h showed that CBT/ΔCBT, WT and CLT in HHS, MHS > control (P<0.001) while FT and CT showed a different trend (HHS > MHS > NC, P<0.001). Exposure of broiler chickens to 3 hours of HHS had dramatic effects on core and surface body temperatures. The effects of MHS were initially more modest yet, after a further 3 hours exposure, resulted in an increase in CBT which was close to that which HHS birds experienced after just 3 hours. This illustrates that duration of exposure to heat stress can have a critical effect, achieving similar life-threatening changes in body temperature that were observed under higher levels of heat stress but for half the time.